Stabilization of Curcumin by Complexation with Divalent Cations in Glycerol/Water System - Bachar Zebib; Zéphirin Mouloungui; Virginie Noirot (Bioinorganic Chemistry and Applications)
The purpose of present study was to stabilize curcumin food pigment by its complexation with divalent ions like (Zn2+,Cu2+,Mg2+,Se2+), in “green media” and evaluate its stability in vitro compared to curcumin alone. The curcumin complexes were prepared by mechanical mixture of curcumin and sulfate salts of each metal (metal : curcumin 1/1mol) into unconventional and nontoxic glycerol/water solvent. Two stoichiometry of complex were obtained, 1 : 1 and 1 : 2 (metal/curcumin), respectively. On evaluation of in vitro stability, all complexes were found to provide a higher stability from curcumin alone.